Design of the female boots using specialized graphics programs - Chertenko, L.; Tarnovetska, Y. (Theory and practice of design, 2015)
The article is devoted to the development of new improved way of creating women boot design with the help of Delcam Crispin on the basis of anthropometric parameters and requirements of modern design. With this aim some research concerning the detection of dependence of boots shape-forming parameters on the height of heel and the parameters of shank was conducted.